2021
DOI: 10.29024/ijsm.64
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmia Related to Remdesivir in COVID-19

Abstract: Background: Remdesivir has shown a positive impact on patient's clinical improvement with COVID-19 and could represent and future viral infections.Results: 16 out of 37 patients presented bradycardia, 4 of these patients had QTc > 450 ms. Infusion for 3 days or more of infusion had a higher incidence of bradycardia (12 vs 4 patients). Overall, patients without bradycardia had a longer hospitalization (20.5 vs 15.5 days); 7 patients died, 2 of them had bradycardia. Conclusion:Our results have shown clear eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…As a result of the observed better prognosis, the authors suggest that RDV should be continued, but with increased measures of patient surveillance. This observation of a more favorable outcome among those with bradycardia was also documented in the descriptive retrospective study by Rodriguez-Guerra et al, which found that patients with bradycardia had a shorter hospitalization (15.5 vs. 20.5 days) [25].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As a result of the observed better prognosis, the authors suggest that RDV should be continued, but with increased measures of patient surveillance. This observation of a more favorable outcome among those with bradycardia was also documented in the descriptive retrospective study by Rodriguez-Guerra et al, which found that patients with bradycardia had a shorter hospitalization (15.5 vs. 20.5 days) [25].…”
Section: Discussionsupporting
confidence: 67%
“…Several cohort studies using real-world data have investigated the relationship of RDV and bradyarrhythmia in COVID-19 patients but did not meet the inclusion criteria for the present study. A retrospective cohort study from BronxCare Hospital Center of 37 COVID-19 patients who received RDV therapy found that 43% (n = 16) developed bradycardia [ 25 ]. The investigators found a higher incidence of bradycardia in patients who received infusion for three or more days, which is consistent with other reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3c) and ivermectin increased over time since September 2021, and the turning point for remdesivir came at almost the same time of emerging studies showing that the drug is ineffective [31] and has severe side effects. [32][33][34] For ivermectin, public sentiment was associated with announcements of health authorities and celebrity effects. For example, the FDA denouncing the use of ivermectin for COVID-19 on August 29 th , 2021 had simultaneously increasing negative discussions.…”
Section: Changes In Sentiment For Five Most Frequent Mentioned Drugsmentioning
confidence: 99%